Integrating Ethnomathematics Through Traditional Maluku Snacks to Enhance Geometric Understanding of Junior High Students - Purba, Pratiwi Bernadetta; Nurwijaya, Sugian (Universitas Muhammadiyah Mataram, 2024)
This study explores the potensial of utilizing traditional Maluku snacks (pom poms, bagea, embal kacang, sagu lempeng, serut kenari) as pedagogical tools to enhance students’ understanding of geometric conceps. The aim of this research is to describe how to integrate Ethnomathematics through traditional Maluku snacks to improve junior high school students' understanding of geometry concepts. This research was carried out in November 2023 at Yos Sudarso Junior High School Dobo. The subjects in this research were 30 grade 8 students. In this research, students used traditional Maluku snacks to understand geometric concepts through demonstrations and discussions. This research uses a qualitative approach where the type of research is descriptive qualitative. The data collection technique in this research is through observation using students’ worksheets, interviews, and documentation using a recording device. Furthermore, data analysis in this research is qualitative analysis with stages of data reduction, data presentation, and drawing conclusions. The results of the research are that students understand the concept of 2D shapes in traditional Maluku snacks: pom-poms (triangles and rectangles), bagea (circles), serut kenari (circles and rectangles), sagu lempeng (trapezoids and rectangles), and embal kacang (rectangle). The concept of 3D shapes in traditional Maluku snacks: pom-poms (triangular prisms), bagea (balls), serut kenari (tubes), sagu lempeng (trapezoidal prisms), and embal kacang (cube-shaped). The integration of ethnomathematics in learning can include learning experiences to the formation of mathematical concepts, especially geometry, mathematical problems, the use of terms in geometry. It is hoped that the integration of ethnomathematics in geometry learning at school can develop meaningful learning.